Shifts and twists in the relative productivity of skilled labor - Arnaud Dupuy; Philip S. Marey (Institute for the Study of Labor (IZA), 2007)
Skill-biased technical change is usually interpreted in terms of the efficiency parameters of skilled and unskilled labor. This implies that the relative productivity of skilled workers changes proportionally in all tasks. In contrast, we argue that technical changes also affect the curvature of the distribution of relative productivity. Building on Rosen's (1978) tasks assignment model, this implies that not only the efficiency parameters of skilled and unskilled workers change, but also the elasticity of substitution between skill-types of labor. Using data for the United States between 1963 and 2002, we find significant empirical support for a decrease in the elasticity of substitution at the end of the 70s followed by an increase at the beginning of the 90s. This pattern of the elasticity of substitution has contributed to the labor productivity slowdown in the mid 70s through the 80s and to a speedup in the 90s.
urn:nbn:de:101:1-20080410234
Keywords: 330; Qualifikation; Technischer Fortschritt; Arbeitsproduktivität; Facharbeiter; Ungelernte Arbeitskräfte; Substitutionselastizität; USA